ALGORITHM STUDY ZERO INFLATED POISSON AUTOREGRESSION MODEL FOR R PROGRAM, CASE STUDY: THE NUMBER OF EARTHQUAKES AT SULAWESI ISLAND - WIRADANA (10112064), IVAN
Earthquake is a natural phenomenon at Sulawesi because Sulawesi is in Ring of Fire area. The number of earthquakes that occur always become concern, because it can affect building and population at Sulawesi. So the decision to anticipate the huge loss is to estimate amount of the earthquake. We can treat the number of earthquakes as counting data and stochastic process with time parameter index. Zero Inflated Poisson Autoregression is one of the appropriate model for number of earthquakes. Besides the number of earthquakes contain many zeros data, earthquakes also dependent event that affect the chance of quake depend on last quake. Hence, modeling with Zero Inflated Poisson Autoregression for the number of earthquakes expected can help predict the number of earthquakes in the future.